The Effects of Rosiglitazone on Task Specific Anxiety-Like Behavior and Novelty Seeking in a Model of Chronic Adolescent Unpredictable Stress - Sexton, Hannah G.; Olszewski, Nathan A.; Risher, Mary-Louise (Frontiers in Behavioral Neuroscience, 2022)
Adolescence is characterized as a period of increased social behavior, risk taking, and novelty seeking, partly due to ongoing maturation in critical brain areas and the hypothalamic-pituitary-adrenal (HPA) negative-feedback system. During this period there is heightened vulnerability to stress that can drive neuro-immune-endocrine remodeling, resulting in the emergence of maladaptive behaviors that increase susceptibility to alcohol and substance abuse. Here we used a rat model to investigate the impact of chronic adolescent unpredictable stress on a battery of behavioral measures to assess novelty seeking, risk taking, depression, and voluntary ethanol consumption while determining whether the PARRγ agonist rosiglitazone can attenuate these effects. Adolescent female rats that experienced stress showed increased risk taking behavior and novelty seeking behavior with no change in ethanol consumption. The administration of rosiglitazone during stress induction attenuated stress-induced cortisol elevation, risk taking, and novelty seeking in a task-specific manner. Depressive-like behavior was not impacted by adolescent unpredictable stress or the administration of rosiglitazone. The results from this study demonstrate that exposure to unpredictable stress during adolescence increases the prevalence of maladaptive behaviors that are known to increase susceptibility to alcohol and substance abuse, and that rosiglitazone may be an effective therapeutic to attenuate the emergence of select risk taking and novelty seeking behaviors in females.